2013
DOI: 10.1037/a0031172
|View full text |Cite
|
Sign up to set email alerts
|

Focused, unfocused, and defocused information in working memory.

Abstract: The study investigated the effect of selection cues in working memory (WM) on the fate of not-selected contents of WM. Experiments 1A and 1B showed that focusing on 1 cued item in WM does not impair memory for the remaining items. The nonfocused items are maintained in WM even when this is not required by the task. Experiments 2 and 3 showed that items that were once focused in WM remain strengthened after the focus shifts away from them. When defocused items are presented as mismatching recognition probes, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
189
5
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(234 citation statements)
references
References 76 publications
30
189
5
1
Order By: Relevance
“…Finally, recent results show that repeated retro-cueing during the retention interval resulted in better memory performance for the repeatedly cued item as compared to single cues, suggesting that spatial retro-cues can strengthen memory representations (Rerko & Oberauer, 2013). Here, we observed a similar result: a valid retro-cues further added to the effect of the pre-cue.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Finally, recent results show that repeated retro-cueing during the retention interval resulted in better memory performance for the repeatedly cued item as compared to single cues, suggesting that spatial retro-cues can strengthen memory representations (Rerko & Oberauer, 2013). Here, we observed a similar result: a valid retro-cues further added to the effect of the pre-cue.…”
Section: Discussionsupporting
confidence: 82%
“…Whereas spatial retro-cues are known to strongly affect the content of visual memory (Astle et al, 2012;Griffin & Nobre, 2003;Landman et al, 2003;Makovski, Sussman, & Jiang, 2008;Murray, Nobre, Clark, Cravo, & Stokes, 2013;Rerko & Oberauer, 2013;Rerko, Souza, & Oberauer, 2014;Sligte et al, 2008), few studies have addressed the role of FBA during VSTM maintenance. In these studies, colored retrocues identified one of several colored objects held in memory and participants reproduced their orientation (Heuer & Schubö, 2016;Li & Saiki, 2015;Pertzov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…These findings converge with other studies that have observed that one item can be retained in a privileged state (of heightened accessibility) even when other items are cued between the initial cueing and testing (Rerko & Oberauer, 2013;Souza, Rerko, & Oberauer, 2015) or are subsequently encoded into WM (Gorgoraptis, Catalao, Bays, & Husain, 2011;. In sum, focused attention can be used to prioritize one WM item in a manner that is robust against distractions from the external or internal focus of attention.…”
Section: Resistance To Distractionsupporting
confidence: 72%
“…When a second retro-cue follows the first, and the last-cued item is the one relevant to the test, a retro-cue benefit is observed for the second-cued item (Landman et al, 2003;Li & Saiki, 2014;Maxcey, Fukuda, Song, & Woodman, 2015;Rerko & Oberauer, 2013). When all of the sequentially cued items are relevant, improvements have been reported for all cued items (Li & Saiki, 2014;, and this improvement is larger, the more frequently the same item is cued during the retention interval .…”
Section: Splitting Attention Between Multiple Wm Itemsmentioning
confidence: 68%
See 1 more Smart Citation